2020
DOI: 10.1016/j.celrep.2020.107802
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast-Derived STC-1 Modulates Tumor-Associated Macrophages and Lung Adenocarcinoma Development

Abstract: Highlights d STC1 is expressed and secreted from TAFs d STC1 depletion results in an accumulation of mature TAMs and TAFs in mouse lung models d Fibroblast-derived STC1 binds to GRP94, preventing macrophage differentiation d STC1 high human lung adenocarcinomas have increased unpolarized TAMs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 77 publications
(107 reference statements)
0
32
0
Order By: Relevance
“… 339 The CAF–TAM interaction was also regulated by pleiotropic glycoprotein stanniocalcin-1, which was secreted by CAFs and partially suppressed TAM differentiation. 340 In colorectal cancer, CAFs could attract monocytes via IL-8/CXCR2 pathway to induce their polarization. 341 Thus, CAFs play crucial roles in shaping the immunosuppressive TME by educating TAMs to induce a protumor phenotype, and methods for reversing CAF-mediated immunosuppression in TAM-targeted therapeutics need to be considered.…”
Section: Immunotheray Driven By Cafsmentioning
confidence: 99%
“… 339 The CAF–TAM interaction was also regulated by pleiotropic glycoprotein stanniocalcin-1, which was secreted by CAFs and partially suppressed TAM differentiation. 340 In colorectal cancer, CAFs could attract monocytes via IL-8/CXCR2 pathway to induce their polarization. 341 Thus, CAFs play crucial roles in shaping the immunosuppressive TME by educating TAMs to induce a protumor phenotype, and methods for reversing CAF-mediated immunosuppression in TAM-targeted therapeutics need to be considered.…”
Section: Immunotheray Driven By Cafsmentioning
confidence: 99%
“…56 Alternative depleting agents have also been successfully investigated in MPM models, 54 71 while our own work has also identified the fibroblast-derived secreted protein STC1 as an additional regulator of TAM differentiation in lung adenocarcinoma. 72 By contrast, reprogramming strategies attempt to stimulate TAMs to repress their protumor functions and switch to a phagocytic role. A reprogramming function of CSF-1R inhibition has been proposed in glioma, which results in downregulation of M2-like markers, 73 possibly by diverting classical monocyte maturation from the CSF-1 to the CSF-2 pathway.…”
Section: Targeting Tams In Novel Mpm Immunotherapiesmentioning
confidence: 99%
“…TAM-like F4/80+ cells (Kamata et al, 2020;Franklin et al, 2014) were the sole cell populations in the stroma significantly decreased by atorvastatin when compared as relative percentages (Fig. 3D) suggesting that, as with the BRAF V600E model, these are the primary cell targets of atorvastatin.…”
Section: Disease Models and Mechanisms • Dmm • Accepted Manuscriptmentioning
confidence: 77%
“…1C). Quantitative analysis of CD11c+ stromal immature macrophage lineage cells (IMCs) and surfactant protein-C (SPC)+ adenoma cells using flow cytometry (Kamata et al, 2015;Kamata et al, 2020) confirmed that both cell types were robustly decreased by atorvastatin treatment (Fig. 1D).…”
Section: Atorvastatin Inhibits Braf V600e -Driven Lung Adenoma Developmentmentioning
confidence: 82%